PENGARUH KETERSEDIAAN RUANG TERBUKA HIJAU TERHADAP TINGKAT KENYAMANAN TERMAL DI WILAYAH PERKOTAAN (Studi Kasus di Kelurahan Sokanegara, Kota Purwokerto) - Asri Sekar Ningrum; Muhamad Khairul Rosyidy; Novia Rahmat Desti Sukmawati; Ike Widia Ariani; Astrid Damayanti (Jurnal Meteorologi Klimatologi dan Geofisika, 2020)
Population increasing in the city of Purwokerto affects the increase in built-up area and reduced vegetation areas or Green Open Space (RTH). According to the Ministry of Public Works, urban areas must provide green open space (RTH) as much as 30% of the total area. The condition of Green Open Space (RTH) and its availability is important for a city because it will greatly affect the environmental conditions and microclimate around the area. This study aims to determine the availability of Green Open Space (RTH) in urban areas and its effect on the level of thermal comfort by emphasizing the Sokanegara, Purwokerto City. The data used is the Sentinel-2A satellite image data acquisition of 12 September 2019, for analysis of the distribution of green open spaces using the NDVI (Normalized Difference Vegetation Index) algorithm. The method to get the level of thermal comfort is to use the THI (Thermal Humidity Index) index. The results indicated that all types of green open space in Sokanegara sub-district categorized as uncomfortable because the THI value at each sample point of green open space is more than 28 â„ƒ. Therefore, further planning is needed to increase the Green Open Space in Sokanegara Village, East Purwokerto.